Penyuluhan Tentang Peremajaan Kelapa Sawit dan Legalitas Lahan Di Kecamatan Kempas Kabupaten Indragiri Hilir - Mulono Apriyanto; KMS Novyar Satriawan Fikri; Vivi Arfiani Siregar; Jamri; Ali Azhar (JPM: Jurnal Pengabdian Masyarakat, 2020)
The specific objectives and targets of these community service activities are to provide counseling on the rejuvenation of oil palm and the legality of farmers' land so that there is a change in the knowledge, understanding and skills of farmers who are members of farmer groups in an effort to want to rejuvenate oil palm plants and to provide an understanding of the importance of legality Farmer's land as an inseparable part of the structure of the requirements in order to get financial assistance to rejuvenate oil palm plants. The methods used are counseling, outreach, demonstration and assistance when the extension activities take place. Counseling methods provide counseling and conduct training after counseling. The demonstration method is carried out at the time of delivery of material. Farmers immediately practiced how to rejuvenate oil palm plants, after that they were given counseling about the ways and functions of farmers' land legality and farmer group institutions in order to get funds in groups. The assistance method aims to monitor developments after counseling to farmers by involving agents of change, namely community leaders, traditional leaders, the village government and banking institutions. In general, the implementation of community service in Kerta Jaya and Tassel Jaya villages, Kempas Subdistrict, Indragiri Hilir Regency can run well and well